Nanopore sequencing of RAGE gene polymorphisms and their association with type 2 diabetes - Chaurasiya, Arvindkumar H.; Khilari, Ajinkya A.; Kazi, Rubina; Jaiswal, Meera R.; Bhoite, Gouri M.; Padwal, Meghana K.; Momin, Abdulrahaman A.; Shanmugam, Dhanasekaran; Kulkarni, Mahesh J. (ACS Omega, 2023)
The receptor foradvanced glycation end products (RAGE)is a transmembraneprotein that interacts with its ligands, advanced glycation end products(AGEs). AGEs are elevated in diabetes and diabetic complications,leading to increased oxidative stress and activation of pro-inflammatorypathways facilitated by AGE-RAGE signaling. Polymorphisms inthe RAGE gene can potentially affect AGE-RAGEinteraction and its downstream signaling, which plays a crucial rolein the progression of diabetes and its complications. In this study,we used nanopore sequencing for genotyping of RAGE polymorphism and identified a maximum number of 33 polymorphisms,including two previously unreported novel mutations in a cohort ofhealthy, type 2 diabetics without nephropathy and type 2 diabeticswith nephropathy in order to identify associations. Two novel RAGE polymorphisms in the intron 8 and 3 & PRIME;UTR regionat genomic locations 32181834 and 32181132, respectively, were detectedwith a low frequency. For four previously reported polymorphisms,cross-validation by PCR-RFLP showed 99.75% concordance with nanoporesequencing. Analysis of genotype distribution and allele frequenciesrevealed that five single nucleotide polymorphisms, i.e., rs1800625,rs3131300, rs3134940, rs2070600, and rs9391855, were associated withan increased risk for type 2 diabetes.

Expanding the Egbenema horizon: Novel species discovery in India and first complete genome assembly of the genus - Bhagat, Jayesh M.; Khilari, Ajinkya A.; Shanmugam, Dhanasekaran; Patankar, Meena (Algal Research-Biomass Biofuels and Bioproducts, 2025)
The recognition of Egbenema bharatensis, a novel species of cyanobacteria from the Northern Western Ghats, extends the ecological and phylogenetic understanding of the genus Egbenema and highlights terrestrial microbial diversity of the region. Morphological characterization revealed resemblance with other Egbenema species but was inconclusive for definitive taxonomic classification. Preliminary phylogenetic analysis based on 16S rRNA gene sequences indicated affiliation with the genus but showed less than 98 % similarity to known species, pointing toward taxonomic distinctiveness. Analysis of the 16S-ITS region further supported this differentiation, revealing unique secondary structural features. Based on these findings, we propose the isolate as a novel species within Egbenema. Whole-genome sequencing provided full resolution and functional genome annotation revealed nitrogen fixation, cobalamin biosynthesis, and stress tolerance pathways, suggesting its metabolic versatility and potential biotechnological applications. The presence of multiple toxin-antitoxin systems also reflects its adaptability to environmental fluctuation. This study also presents the first complete genome of the genus Egbenema, filling a significant gap in cyanobacterial genomic resources. These findings encourage integrative taxonomic practices and affirm the significance of exploring biodiversity hotspots for uncovering cryptic microbial diversity with ecological and industrial potential.
Keywords: 16S rRNA; Biodiversity hotspots; Cyanobacteria; Egbenema bharatensis; ITS secondary structure; Northern Western Ghats; whole-genome sequencing